2020
DOI: 10.21203/rs.3.rs-113852/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of SARS-CoV-2 Antigen-Based Rapid Diagnostic Kits in Pakistan: Formulation of COVID-19 National Testing Strategy.

Abstract: Rapid diagnosis of SARS-CoV-2 during pandemic enables timely treatment and prevention of COVID-19. Evaluating the accuracy and reliability of rapid diagnostic testing kits is crucial for surveillance and diagnosis of SARS-CoV-2 infections in general population, injection drug users, multi-transfused populations, healthcare workers, prisoners, barbers and other high risk populations. The aim of this study was to evaluate performance and effectiveness of nasopharyngeal swab (NSP) and saliva based rapid antigen d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…During the second wave of COVID-19 we aimed to re-investigate new COVID-19 testing RDT diagnostic kits. In continuation of our previous study(6), current study indicated that in comparison to gold standard, RT-PCR based COVID-19 detection kit, the nasal RDT showed improved 78 % sensitivity, while 21% showed false negative results. The NSP based RDTs kit showed zero cross reactivity against Human metapneumovirus, Mumps virus, Rotavirus, Adenovirus, Epstein-Barr virus, human Coronavirus OC43, Mycoplasma pneumonia Varicella Zosyer virus, Respiratory Syncytial virus, Cytomegalovirus, Measels virus, In uenza viruses and Norovirus.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…During the second wave of COVID-19 we aimed to re-investigate new COVID-19 testing RDT diagnostic kits. In continuation of our previous study(6), current study indicated that in comparison to gold standard, RT-PCR based COVID-19 detection kit, the nasal RDT showed improved 78 % sensitivity, while 21% showed false negative results. The NSP based RDTs kit showed zero cross reactivity against Human metapneumovirus, Mumps virus, Rotavirus, Adenovirus, Epstein-Barr virus, human Coronavirus OC43, Mycoplasma pneumonia Varicella Zosyer virus, Respiratory Syncytial virus, Cytomegalovirus, Measels virus, In uenza viruses and Norovirus.…”
supporting
confidence: 76%
“…Recently, from Pakistan nasal and saliva based RDTs revealed sensitivities of 52% and 21% respectively (6). The current study revealed that RT-PCR analysis from study enrolled subjects (during second COVID-19 wave) revealed that prevalence rate of COVID-19 during the period of November in Islamabad/Rawalpindi region of Pakistan was 6.67%, which is 22 times higher than COVID-19 prevalence during October 2020 (6).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations